2018
DOI: 10.1002/cjp2.106
|View full text |Cite|
|
Sign up to set email alerts
|

Stanniocalcin 2 expression is associated with a favourable outcome in male breast cancer

Abstract: Breast cancer can occur in either gender; however, it is rare in men, accounting for <1% of diagnosed cases. In a previous transcriptomic screen of male breast cancer (MBC) and female breast cancer (FBC) occurrences, we observed that Stanniocalcin 2 (STC2) was overexpressed in the former. The aim of this study was to confirm the expression of STC2 in MBC and to investigate whether this had an impact on patient prognosis. Following an earlier transcriptomic screen, STC2 gene expression was confirmed by RT‐qPCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…STC2 also suppressed breast cancer cell migration and invasion by PKC/claudin1 mediated signaling (41,43). STC2 expression was also associated with positive outcome in male breast cancer (79). Taken together, except in breast cancer, STC2 expression is a potential prognostic marker for variety of cancers which promotes tumor cell growth, invasion and migration.…”
Section: Tumor Biologymentioning
confidence: 84%
“…STC2 also suppressed breast cancer cell migration and invasion by PKC/claudin1 mediated signaling (41,43). STC2 expression was also associated with positive outcome in male breast cancer (79). Taken together, except in breast cancer, STC2 expression is a potential prognostic marker for variety of cancers which promotes tumor cell growth, invasion and migration.…”
Section: Tumor Biologymentioning
confidence: 84%
“…49 Differential gene expression analysis of patient subgroups with good versus bad survival (based on 4 independent signatures of apoptotic proficiency) identified 11 genes similarly enriched in either of these groups, 8 of which had previously been attributed an impact on breast cancer progression or patient survival ( Figures 5 and 6). 34,[37][38][39][40][41][42][43] The expression levels of these genes also conveyed prognostic value in patients from the METABRIC dataset ( Figure 6 and Tables 1and 2), with the potential exception of CYP4X1. Of the remaining three genes, LTB failed to impact cancer-specific overall survival in the METABRIC cohort (Tables 1 and 2), while both CLIC6 and SLC7A2 were strongly associated with improved disease outcome ( Figure 6 and Tables 1 and 2), although only SLC7A2 as an independent prognostic biomarker ( Table 2).…”
Section: Discussionmentioning
confidence: 96%
“…Strikingly, 7 of these 11 genes have previously been attributed an impact on breast cancer progression and patient survival that is in line with our findings. These genes are AGR3, 34 ANKRD30A, 35 BMPR1B, 36,37 STC2 38,39 and SUSD3, 40 which are all indicators of early disease or good prognosis, as well as CXCL9, 41,42 and CALML5, 43 both of which have previously been linked to disease progression or poor prognosis. Conversely, CYP4X1 (which is our hands was enriched in patients with good survival) has previously been positively correlated with tumor grade.…”
Section: Signatures Of Apoptotic Proficiency Convey Negative Prognostmentioning
confidence: 99%
“…It is highly important to identify new colorectal cancer (CRC) treatment targets. It has been reported that stanniocalcin 2 (STC2) is involved in the progression of various types of cancer, such as gastric and breast cancer (22,23). The differential expression levels of STC2 have certain guiding significance for the prediction, metastasis and prognosis of various malignant tumors (24).…”
Section: Discussionmentioning
confidence: 99%